Impact of plug-in electric vehicles on grid integration with distributed energy resources: A review - Dharavat, Nagaraju; Golla, Naresh Kumar; Sudabattula, Suresh Kumar; Velamuri, Suresh; Kantipudi, M. V. V. Prasad; Kotb, Hossam; AboRas, Kareem M. (Frontiers in Energy Research, 2023)
The rise of electric vehicles (EVs) has a massive impact on the electricity grid due to the electrification of vehicles in the transportation sector. As a result, various techniques are needed to minimize the effects of charging on the grid. One of these techniques is having intelligent coordination between the various components of the EV charging network. This ensures that the network has enough electricity to support the charging needs of the vehicles. This article provides an overview of the many aspects of the EV industry and its charging infrastructure. It also provides a step-by-step approach for implementing the Vehicle to Grid (V2G) deployment, the utilization of recordings from the data by the EV battery through Artificial Intelligence and the cost-benefit analysis from effective utilization of the V2G method. The paper also explores the various aspects of the EV market and the role of aggregators and consumers. Finally, it assesses the possibility of expansion of the EV charging and grid integration system and outlines its challenges and solutions.